Characteristics of Stress Field and Damage Law of Coal Rock in Residual Pillar of Top Slice and Its Application - Wu, Fengfeng; Yu, Xin; Zhao, Gaoliang; Du, Beiju; Lv, Bo; Zhang, Jian (Frontiers in Earth Science, 2022)
In view of the problem of determining the reasonable position of the lower slice roadway in the residual pillar area after the top slice of thick coal seam, the load concentration of the coal pillar and the floor of the goaf under different caving conditions and the stress distribution characteristics of the coal pillar area before and after the top slice are studied by using the method of theoretical analysis and numerical simulation. The mechanical model of the residual pillar load propagation in the floor and the failure model of the floor surrounding rock are constructed, and the analytical formula of the coal pillar floor stress and the expression of the floor failure depth of the roadway are deduced, which provides a basis for the reasonable determination of the position of the lower slicing roadway. Studies prove that: After the mining of the top-slice working face, the floor stress field of the residual pillar area presents the characteristics of non-uniform distribution. The stress concentration area appears below the coal pillar, the stress variation area appears at the edge of the coal pillar, and the stress stable area appears far away from the coal pillar area. The roadway layout should avoid the areas below the coal pillar and the coal pillar edge with high stress level and large stress variation gradient. Formation of high stress concentration on coal pillar and transfer to lower layered coal and floor strata, and decrease of stress concentration layer by layer. Affected by the mining of top layered working face, the coal and rock mass in the coal pillar floor area is damaged and the mechanical properties are weakened, which is not conducive to the control of roadway surrounding rock. The research results have been applied in No. 30117 working face of the lower slice of Shancheng Coal Industry, and the reasonable position of the return airway of the working face was determined to be 8m outside the east side of the residual pillar in the top slice, and good surrounding rock control effect has been achieved.